Use of Cerebrospinal Fluid (1, 3)-β-D-Glucan to Monitor Treatment Response in Candida albicans Meningitis in an HIV-infected Patient. Issue 6 (November 2018) - Moran, Caitlin A.; Terry, Charles; Nguyen, Minh Ly T.; Sheth, Anandi N.
Abstract : Abstract: Candida meningitis is rare in the setting of human immunodeficiency virus (HIV) infection and often presents a diagnostic challenge. Its clinical features typically mimic those of cryptococcal or tuberculous meningitis and Candida can be difficult to culture from cerebrospinal fluid. Furthermore, optimal treatment and monitoring parameters are not well defined. Cerebrospinal fluid levels of (1, 3)-β-D-glucan, which is a component of the fungal cell wall, have been used to diagnose and monitor response to therapy in other cases of fungal meningitis, but its utility in the setting of Candida meningitis and HIV infection is less clear. Here, we present a case of spontaneous Candida albicans meningitis in a woman with advanced HIV infection and report on the clinical utility of cerebrospinal fluid (1, 3)-β-D-glucan for diagnosis and monitoring of chronic infection. Abstract : Spontaneous Candida albicans meningitis is rare in the setting of HIV infection and can be prolonged and difficult to treat. Cerebrospinal fluid (CSF) culture can be unreliable and slow in monitoring treatment response. The authors present a case in which CSF (1, 3)-β-D-glucan was used successfully to monitor treatment response in a patient with HIV and chronic Candida meningitis, which may have implications for the diagnosis of future cases.